SUPEROVULATORY RESPONSE IN CROSSBRED COWS WITH MULTIPLE VERSUS SINGLE INJECTION OF FSH DISSOLVED IN POLYVINYLPYRROLIDONE - KARUNAKARAN, M; VEERAPANDIAN, C; SUBRAMANIAN, A; KATHIRESAN, D; DHALI, A; BHATT, B P; MANOKARAN, S (The Indian Journal of Animal Reproduction, 2023)
The use of a single FSH injection for inducing superovulation in cow is desirable. In this study weexamined whether dissolving FSH in polyvinylpyrrolidone (PVP) would reduce the rate of absorption ofFSH and allow it to be administered in a single dose for superovulation. Crossbred cows (n= 9 in eachgroup) were superovulated either with a single intra-muscular injection of 18 mg FSH dissolved in 1 0 mlof 30 % PVP or with 18 mg of FSH dissolved in saline given as eight intra-muscular injections over fourdays period. Prostaglandin F 2alpha  was given to all the cows 48 h after the first FSH injection. The cowswere inseminated with frozen semen at 12 and 24 h following the estrus onset. Superovulatory responsewas assessed by palpation per rectum on day 7 post breeding and the cows with more than 2 corpusluteum (CL) were flushed. Progesterone level in the blood samples collected on the day of first FSH injection and on the day of embryo collection were found to be significantly (P
Keywords: Superovulation; Cows; FSH; PVP